Comparative Genomic Analysis of the 2016 Vibrio cholerae Outbreak in South Korea - Ha, Sung-min; Chalita, Mauricio; Yang, Seung-Jo; Yoon, Seok-Hwan; Cho, Kyeunghee; Seong, Won Keun; Hong, Sahyun; Kim, Junyoung; Kwak, Hyo-Sun; Chun, Jongsik (Frontiers in Public Health, 2019)
In August 2016, South Korea experienced a cholera outbreak that caused acute watery diarrhea in three people. It was the first time in 15 years that the outbreak was not related to an overseas source. To track down the cause and find the epidemiological relevance of this outbreak, we sequenced the whole genomes of Vibrio cholerae isolates, three from patients and one from a seawater sample. Comparative genomic analysis revealed that the genome sequences of the four isolates are highly similar and form a monophyletic clade with V. cholerae strains that have caused an outbreak in the Philippines in 2011. The Korean and Philippines outbreak strains have almost identical gene contents in which two unique genomic islands are shared, and they both lack SXT elements. We have confirmed that seawater is the likely source of this outbreak, which strongly suggests the necessity for future routine surveillance of South Korea’s seashore.